MARKETING STRATEGY OF UMRAH BANNER PRODUCTS IN INCREASING THE NUMBER OF PROSPECTIVE PILGRIMAGES DURING COVID 19 AT SAMIRA TRAVEL SIDOARJO - Nur Iza Faizah; Masruchin Masruchin (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study aims to evaluate the marketing strategies implemented by PT. Samira Utama Wisata (Samira Travel) to increase the sales of its Talangan Umrah product during the Covid-19 pandemic. Background: The global pandemic led to the temporary suspension of Umrah pilgrimages in mid-2020, resulting in a sharp decline in demand for travel services. In response, Samira Travel introduced an innovative financing product—Talangan Umrah—designed to assist customers in fulfilling their religious pilgrimage aspirations amid financial constraints. Method: The research employs a descriptive qualitative approach, with data obtained through interviews and documentation at the Samira Travel branch office in Sidoarjo. Findings: The results indicate that Samira Travel effectively utilized digital marketing strategies, leveraging social media platforms and online promotional campaigns to maintain visibility and attract customer interest. Additionally, the company enhanced communication with potential pilgrims through multiple channels, including telephone, WhatsApp, and the official company website. Conclusion: The study concludes that the integration of digital marketing and direct communication strategies played a crucial role in sustaining customer engagement and promoting the Talangan Umrah product during the pandemic, offering valuable insights for marketing resilience in times of crisis.